Penerapan Model Pembelajaran Group Investigasi (GI) Dalam Meningkatkan Kemampuan Kognitif Siswa - Runengtih, Runengtih; Setiawati, Ina; Lismaya, Lilis (Edubiologica, 2020)
The study aims to determine the application of the Investigasi Group learing model in improving the cognitive abilities of students in natural sciences subjects, namely the Excretion System material. This research is a Quasi eksperimental study, with a nonquivalent control group desaign. The population of this study was all students of class VIII 2018/2019 achool year. The research sample is one eksperimental class as a control class. Hypotesis testing using parametric statistical tests using t test obtained tcaount > ttable is 9,337 > 2,682, which means learning using the Group Investigasi model can improve cognitif abilities. Cognitive ability test results abtained the percentage of the average value for the experimental class that is 58,85. N gain results for the medium category and for the control class 0,40 in the medium  category. Form the results of the questionnaire data analysis as many as 89 % of students agreed that tehe Investigasi Geoup model could increase learining motivation. The results showed there was an increase in cognitive abilities in students using the Group Investigasi model